STUDY OF THE INFLUENCE OF PERSONAL CHARACTERISTICS ON THE STATUS OF TEENAGERS IN THE GROUP - Demchenko, Natalia; Proskurka, Natalia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The purpose of this study is to study the individual psychological qualities of a teenager as a component that affects various aspects of an individual's activity and interaction with others. A special issue is the study of the socio-psychological status among teenagers and the assessment of individual-psychological qualities that contribute to this. The following methods were used: Kettel's questionnaire for adolescents 14PF; the method "Definition of general self-esteem" by G.N. Kazantseva; test of interpersonal relations T. Leary; socio-psychological test "Sociometry" by J. Moreno.; the method of mathematical data processing - Spearman's rank correlation coefficient. The results. In the course of empirical research, it was established that this sample of teenagers is characterized by extroversion, a balanced level of emotional stability, shyness, energy, an average level of self-control, and weak motivational activity. At the same time, it was established that the largest number of respondents has an adequate self-esteem, followed by respondents with a low level of self-esteem, and the smallest number of respondents has a high level of self-esteem. According to the results of T. Leary's method of identifying the level of interpersonal relations, it was established that teenagers are characterized by such traits as dominance and friendliness. According to the results of the "Sociometry" method by J. Moreno, it was established that according to the results of group elections, the largest number of respondents is a positive choice of the group, and there are no respondents who do not have any choice in the group. Conclusions. Thus, the existence of two-way correlations between the scales of the specificity of the mutual relations of team members and the levels of interpersonal relations was established (р ≤ 0.05). It was also established the existence of two-way correlations between the "friendliness" scales and the number of positive group choices in sociometry (р ≤ 0.05), and between individual properties and character traits and the specifics of team members' relationships (р ≤ 0.05). Thus, it was concluded that the individual and psychological characteristics of adolescents have an impact on their status in the group